DNA polymerase kappa protects human cells against MMC-induced genotoxicity through error-free translesion DNA synthesis. (December 2017) - Kanemaru, Yuki; Suzuki, Tetsuya; Sassa, Akira; Matsumoto, Kyomu; Adachi, Noritaka; Honma, Masamitsu; Numazawa, Satoshi; Nohmi, Takehiko
Abstract Background Interactions between genes and environment are critical factors for causing cancer in humans. The genotoxicity of environmental chemicals can be enhanced via the modulation of susceptible genes in host human cells. DNA polymerase kappa (Pol κ) is a specialized DNA polymerase that plays an important role in DNA damage tolerance through translesion DNA synthesis. To better understand the protective roles of Pol κ, we previously engineered two human cell lines either deficient in expression of Pol κ (KO) or expressing catalytically dead Pol κ (CD) in Nalm-6-MSH+ cells and examined cytotoxic sensitivity against various genotoxins. In this study, we set up several genotoxicity assays with cell lines possessing altered Pol κ activities and investigated the protective roles of Pol κ in terms of genotoxicity induced by mitomycin C (MMC), a therapeutic agent that induces bulky DNA adducts and crosslinks in DNA. Results We introduced a frameshift mutation in one allele of the thymidine kinase (TK) gene of the KO, CD, and wild-type Pol κ cells (WT), thereby establishing cell lines for theTK gene mutation assay, namely TK+/- cells. In addition, we formulated experimental conditions to conduct chromosome aberration (CA) and sister chromatid exchange (SCE) assays with cells. By using the WT TK+/- and KO TK+/- cells, we assayed genotoxicity of MMC. In theTK gene mutation assay, the cytotoxic and mutagenic sensitivities of KO TK+/- cells were higher than those of WT TK+/- cells. MMC induced loss of heterozygosity (LOH), base pair substitutions at CpG sites and tandem mutations at GpG sites in both cell lines. However, the frequencies of LOH and base substitutions at CpG sites were significantly higher in KO TK+/- cells than in WT TK+/- cells. MMC also induced CA and SCE in both cell lines. The KO TK+/- cells displayed higher sensitivity than that displayed by WT TK+/- cells in the SCE assay. Conclusions These results suggest that Pol κ is a modulating factor for the genotoxicity of MMC and also that the established cell lines are useful for evaluating the genotoxicity of chemicals from multiple endpoints in different genetic backgrounds of Pol κ.